Organic coco peat pot suplemented with Black Soldier Frass (BSFF) / Muzaffar Sa’adan, Izzah Nabilah Yusof and Maisarah Samsudin - Sa’adan, Muzaffar; Yusof, Izzah Nabilah; Samsudin, Maisarah (Faculty of Plantation and Agrotechnology, 2023)
The purpose of this research was to generate innovations that are connected to the process that occurs post harvesting. Examine the results of using coco peat as the primary component in the production of organic pots, along with black soldier fly frass, and report your findings (BSFF). When compared to the use of NPK fertilisers in plants, previous research has shown that the use of (BSFF) may result in an increase in biomass. The usage of coco peat as a growing medium for plants may assist in keeping the soil's moisture level stable.